2015
DOI: 10.1097/ico.0000000000000447
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Assessing Nerve Morphology in Central Cornea Versus Whorl Area for Diagnosing Diabetic Peripheral Neuropathy

Abstract: Small nerve fiber pathology is comparable at the central and whorl anatomical sites of the cornea. Quantification of CNFL from the corneal center is as accurate as CNFL quantification of the whorl area for the diagnosis of DPN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 30 publications
0
26
1
1
Order By: Relevance
“…30 Interestingly, the whorl density wCNFL did not vary with presence or duration of diabetes or HbA1c, but was largely preserved. In three recent studies that did not employ widefield mosaicking or depth correction techniques, [31][32][33] reduced CNFL in the whorl region was reported in diabetes-a finding that could not be confirmed in our cohort. In another study, mosaic images indicated a decline in whorl density in diabetes, although the study was limited to only two subjects.…”
Section: Discussioncontrasting
confidence: 54%
“…30 Interestingly, the whorl density wCNFL did not vary with presence or duration of diabetes or HbA1c, but was largely preserved. In three recent studies that did not employ widefield mosaicking or depth correction techniques, [31][32][33] reduced CNFL in the whorl region was reported in diabetes-a finding that could not be confirmed in our cohort. In another study, mosaic images indicated a decline in whorl density in diabetes, although the study was limited to only two subjects.…”
Section: Discussioncontrasting
confidence: 54%
“…Analysis of the sub-basal nerve plexus 44, 45, 46, 47, 48, 49 can be performed in two regions of the cornea: central cornea and the inferior whorl. 50 For example, it has also been reported that the nerve fiber density at the inferior whorl region is more sensitive to early nerve fiber damage than the central corneal region, in DM patients before development of peripheral neuropathy. 51 …”
Section: Cornea Neuropathymentioning
confidence: 99%
“…37 While IVCM is sensitive in detecting corneal subbasal nerve length changes in diabetic neuropathy, neither central corneal subbasal nerve length nor subbasal whorl nerve length have proven to be strong diagnostic tests for diabetic peripheral neuropathy independently (area under the curve, AUC = 0.76–0.77; specificity = 0.5–0.6). 38 However, when taken together, there was moderate improvement in its specificity (0.71) but without an increase in its utility as a diagnostic test (AUC = 0.75). 37 …”
Section: Corneal Subbasal Nerve Plexusmentioning
confidence: 99%